Experience in the use of absorption and biochemical installations for cleaning ventilation emissions in foundry production - A. V. Pribylov; Yu. P. Shapovalov; E. M. Glushen (Литьë и металлургия, 2021)
The relevance of the use of gas cleaning equipment in foundry production is considered. Examples are given of equipping the casting, cooling and knocking areas of molds and rods manufactured according to ALFASET and Cold-box-amin processes with absorption-biochemical installations (ABCHI) for cleaning the ventilation air from pollutants. The technical and economic parameters of the ABCHI operation are considered. The list of the enterprises successfully operating ABHI is given. The advantages of using ABCHI in comparison with alternative methods are considered.